Revisiting the Malvinas Current Upper Circulation and Water Masses Using a High-Resolution Ocean Reanalysis - Artana, Camila Indira; Provost, Christine; Poli, Lea; Ferrari, Ramiro; Lellouche, Jean Michel (Journal of Geophysical Research: Oceans)
We use 25 years of a high-resolution ocean reanalysis (1/12°) to revisit the Malvinas Current (MC) from the South (Drake Passage) to the North (Brazil-Malvinas Confluence) from the synoptic to interannual time scales. The Malvinas Plateau is home to active eddy mixing, eddy dissipation and deep winter mixed layers occasionally reaching 600 m depth. The MC is organized in two jets which merge around 44°S as the continental slope steepens. The upper 900 m transport mean decreases from 40 Sv at 51°S to 35 Sv at 41°S indicating offshore leakage along the MC path. The MC plays a minor role in the velocity variations observed at the Confluence at seasonal and interannual scales; those are driven by changes in the intensity of the Brazil Current over the slope (34–36°S). Computing MC transport time series at different latitudes requires care because the section eastern limits are embedded in an energetic region. Transport time series were produced at selected latitudes using different criteria and showed common features. They show little seasonality (relative seasonal standard deviation of 2%) and no significant trend. The MC is a steady current: the relative standard deviation is on the order of 10% increasing to 20% near and on the Malvinas Plateau and near the Confluence. In contrast, velocity trends are large in the Brazil Current with the overshoot migrating southward. The associated increase in mesoscale activity south of 44°S in the Argentine Basin might contribute to blocking events occasionally reducing the MC transport. Fil: Artana, Camila Indira. Mercator Ocean; Francia. Centre National de la Recherche Scientifique; Francia Fil: Provost, Christine. Universite de Paris VI; Francia Fil: Poli, Lea. Universite de Paris VI; Francia Fil: Ferrari, Ramiro. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Centro de Investigaciones del Mar y la Atmósfera. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Centro de ...